"Hygroma Colli" Sonographic Indication of Chromosomal Abnormality: A Case Report - Hamka Koerslo; Zulmaeta Zulmaeta (Indonesian Journal of Global Health Research, 2025)
This case report aims to highlight the significance of ultrasound imaging in the prenatal diagnosis of hygroma colli, a condition often associated with chromosomal abnormalities, particularly Turner Syndrome (45,XO). A 26-year-old primigravid woman at 17 weeks of gestation was referred for further evaluation of a fetal neck mass detected during routine ultrasound. The sonographic findings revealed a symmetrical, non-septated, hypoechoic cystic mass in the posterolateral region of the fetal neck, along with agenesis of one lung lobe. Based on these findings, pregnancy termination was planned and performed using misoprostol and laminaria insertion. The fetus was delivered with a birth weight of 150 g, a length of 14 cm, and Apgar Score 0/0. Postnatal examination confirmed the presence of hygroma colli, consistent with the ultrasound findings. This case reinforces the importance of early ultrasound screening in identifying fetal anomalies and guiding clinical decisions.